2012
DOI: 10.1021/nn2050278
|View full text |Cite
|
Sign up to set email alerts
|

Copper Can Still Be Epitaxially Deposited on Palladium Nanocrystals To Generate Core–Shell Nanocubes Despite Their Large Lattice Mismatch

Abstract: Here we report the synthesis of Pd@Cu core-shell nanocubes via epitaxial growth, where the lattice mismatch is 7.1%. The synthesis involved the use of Pd seeds with different shapes (including cubes, cuboctahedra, and octahedra) for the epitaxial growth of Cu shells. Different from the conventional growth mode, Cu atoms initially nucleated only on a few of the many faces of a Pd seed, onto which more Cu atoms were continuously added to generate Cu blocks. Later, the Cu atoms also started to nucleate and grow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
217
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(237 citation statements)
references
References 41 publications
16
217
0
4
Order By: Relevance
“…It has been known that to realize epitaxial heterostructures, a small misfit in both lattice symmetry and lattice parameters is usually required to achieve a minimum interfacial energy. Some exceptions have also been reported especially in recent cases of using van der Waals layered materials as substrates which are free from surface dangling bonds to effectively tolerate strains arising from a large symmetry/lattice mismatch [49][50][51][52][53]. Examples include recent demonstrations of epitaxial overgrowth of Pt(101) on MoS 2 (001) [49] and PbSe(001) on Bi 2 Se 3 (001) [50].…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that to realize epitaxial heterostructures, a small misfit in both lattice symmetry and lattice parameters is usually required to achieve a minimum interfacial energy. Some exceptions have also been reported especially in recent cases of using van der Waals layered materials as substrates which are free from surface dangling bonds to effectively tolerate strains arising from a large symmetry/lattice mismatch [49][50][51][52][53]. Examples include recent demonstrations of epitaxial overgrowth of Pt(101) on MoS 2 (001) [49] and PbSe(001) on Bi 2 Se 3 (001) [50].…”
Section: Resultsmentioning
confidence: 99%
“…For example, we found that surface diffusion had a great impact on the asymmetric growth of Cu on a Pd cubic seed. 67 The growth of Cu involved the reduction of CuCl 2 by glucose at 100 °C in the presence of 18-nm Pd cubes as seeds and hexadecylamine as a capping agent for Cu{100} facet. In the initial stage ( Figure 15A), Cu atoms only nucleated and grew on one or two of the side faces of a Pd cubic seed.…”
Section: Symmetry Reductionmentioning
confidence: 99%
“…25 In a very recent work of Xia and co-workers, Cu could still be epitaxially deposited on Pd seeds to form Pd@Cu core-shell nanocubes in hexadecylamine, despite the lattice mismatch between Cu and Pd being 7.1%. 32 This result may be due to the strong affinity between Pd and Cu. Another driving force is the decrease of the surface energy of NCs.…”
Section: Key Factors In Four Routesmentioning
confidence: 99%